Prespektif Demokrasi dalam Al-Qur`an; Fondasi Keadilan dan Pemikiran Partisipatif - Rumni Hafizah; Johari Jamal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
One of the goals of the Qur'an in social life is to create peace and prosperity for mankind by upholding the principles of unity, equality, brotherhood and freedom. Upholding this principle is known as democracy. Democracy can be interpreted as respect for human rights, participation in decision making and equal rights under the law. This research aims to find out how the Koran views democracy. This research was conducted qualitatively using the library method, by analyzing the data descriptively. The results of this research show that the written Qur'an does not mention democracy, but the Qur'an speaks of democracy which includes several things, namely: deliberation (syura), justice ('is), the principle of equality (almusawah), trust and freedom (alhurriyah).